Pasang Surut Inkar Sunnah: Studi Analisis Pada Masa Klasik dan Modern - Syarifah Mudrika; Imamul Authon Nur (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2020)
Although the function of Sunnah is as a second source of Islamic teachings. however, it has been continously debated and even rejected by certain group of people known as inkarusunnah group. The ideology developed in the late of the second century Hijriyah yet it muffled by Imam Shafie until the greatly long period. Unfortunately, during the shift of 19th to 20th centuries, this idea has reemerged and grown up to the present. This article analyzes the development of the ideology using the content analysis method from the various literatures related to the history of InkarSunnah Ideology and movement. This research found the modern InkarSunnah concept is a continuity of the previous movement. According to this group, the rejection of Sunnah due to the fact that Qur’an has cover all matters. In fact, this group lack of understanding on it's real position and function as the second source of Islamic teaching. Whereas, later, they deny it's validity, though it was narrated by a truthful narrators including the companions.